The Perception of Computer Engineering Department Students at Politeknik Negeri Jember towards the Use of Duolingo in Learning English - Vigo Dewangga (Penerbit STKIP PGRI Bangkalan, 2020)
Duolingo application is an online free language educational application. It become more suitable, innovative and applicable way to learn english in EFL classroom. The aim of this study is to find out the students perception towards the use of duolingo application in learning English. The method used in this study is a descrptive research. Then, subject of the study are students at computer engineering department, Politeknik Negeri Jember. The result of this study revealed that computer engineering Department students at Politeknik Negeri Jember come to realize duolingo as a software that is easy to use, interesting and enjoyable for learning English. In addition, duolingo bring a new concept (gamification) in learning English. Thus, it makes them very exciting in learning English.